Health of teenagers in residential care: comparison of data held by care staff with data in community child health records. Issue 1 (1st January 2001) - Bundle, A
Abstract : AIM: To identify whether there are gaps in information available to care staff about the health related needs of one group of teenagers in residential care which could be addressed by reviewing the community child health records. METHODS: Data were collected on the residents of a children's home during a three month period, comparing information from children's home records with information from community child health records. RESULTS: Data were collected from children's home records for 36 residents and child health records obtained for 29. Child health records provided the only information on 53% of child protection registrations and 17.5% of statements of special educational needs. Most information on birth history, developmental and early medical history, immunisations, growth, hearing, and colour vision came from the child health records. Immunisation uptake was below the national average, and particularly poor for BCG and school leaver tetanus, low dose diphtheria, and polio boosters. Emotional and behavioural problems were present in 100% of the residents and this information was known to the home. Poor use of "Looking After Children" records was identified, and there was a paucity of information in the home records and child health records about results of annual looked after medical examinations. CONCLUSION: Important information about the health needs of looked after teenagers was not known to the children's home staff. Community paediatricians should be proactive in identifying and addressing these needs.